1994
DOI: 10.1007/bf00121700
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microstructural features on the biaxial flexural strength of leucite reinforced glass-ceramics

Abstract: In this study the effect of size and distribution of leucite crystals on the biaxial flexural strength of five leucite reinforced glass-ceramics used in dentistry for the construction of veneers was investigated. Three of these were found to have a non-uniform distribution of leucite crystals, which were associated with a considerable degree of microcracking in the glassy matrix around the leucite crystals. The mean values of biaxial flexural strength of these ceramics ranged from 56 to 70 MPa. The other two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 5 publications
(4 reference statements)
0
18
2
2
Order By: Relevance
“…This may be due to the crystalline phases in this material. It has been reported that the crystalline phases in ceramic materials may act as crack stoppers to prevent crack propagation (Shareef et al, 1994). However, with Sensation SL, this was not the case in this study.…”
Section: In Vitro Wear Testing Of All-ceramic Materialscontrasting
confidence: 54%
“…This may be due to the crystalline phases in this material. It has been reported that the crystalline phases in ceramic materials may act as crack stoppers to prevent crack propagation (Shareef et al, 1994). However, with Sensation SL, this was not the case in this study.…”
Section: In Vitro Wear Testing Of All-ceramic Materialscontrasting
confidence: 54%
“…On the contrary, the indirect PFC material -supported by a FRC layer -has an elastic modulus around [12][13][14][15][16][17][18] , which is close to that of dentin (10-20 GPa) 28) . Consequently, this might have resulted in a more homogeneous stress distribution, thereby leading to a higher mean failure load of the tooth-laminate structure.…”
Section: Discussionmentioning
confidence: 99%
“…Incisal chippings and development of cracks are the most common reasons for clinical failures of ceramic veneers 6,[11][12][13] . These failures arose due to the brittle nature of ceramics and their inability to accommodate tensile forces by plastic deformation 14) . Today, stronger and tougher ceramic materials are available, such as Empress 2 (Ivoclar, Vivadent) -a lithium disilicate-reinforced glass ceramic, or Ice Zirkon -a partially yttrium-stabilized zirconium dioxide (Ice Zirkon, ZirkonZahn).…”
Section: Introductionmentioning
confidence: 99%
“…As the crack propagates through the veneering ceramic, the stress concentration is maintained at the crack tip until the crack moves completely through the veneering ceramic causing failure [1,7]. High strength ceramic cores must have a thermal match with the veneering ceramics in terms of the coefficient of thermal expansion (CTE) in order to minimize stresses and crack formation within the material [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%